Reconfigurable Intelligent Surfaces for Doppler Effect and Multipath Fading Mitigation - Basar, Ertugrul (Frontiers in Communications and Networks, 2021)
Owing to the envisioned new use-cases, such as immersive virtual reality and high-fidelity mobile hologram, and their potential challenging new requirements for future wireless networks, extensive research has already started on 6G and beyond wireless technologies. Despite the fact that several modern physical layer solutions have been introduced in the past decade, a level of saturation has been reached in terms of the available spectrum and adapted modulation/coding solutions, which accordingly limits the maximum capacity and reliability. Within this respective, reconfigurable intelligent surface (RIS)-empowered communication appears as a potential candidate to overcome the inherent drawbacks of legacy wireless systems. The core idea of RIS-assisted communication is the transformation of the random and uncontrollable wireless propagation environment into a reconfigurable communication system entity that plays an active role in conveying information and improving system performance. In this paper, the well-known multipath fading phenomenon is revisited in mobile wireless communication systems, and novel and unique solutions are introduced from the perspective of RISs. The feasibility of eliminating or mitigating the multipath fading effect stemming from the movement of mobile receivers is also investigated by utilizing RISs. It is shown that rapid fluctuations in the received signal strength due to the Doppler effect can be effectively reduced by using real-time tunable RISs. It is also proven that the multipath fading effect can be totally eliminated when all reflectors in a propagation environment are coated with RISs. Furthermore, we show that for general propagation environments with several interacting objects, even a few RISs can significantly reduce the Doppler spread and the deep fades in the received signal.